(untitled) - Gregoire, Marc (Indianapolis, IN, 2011)
With this no-nonsense book, you will learn to conquer the latest release of C++. The author deciphers little-known features of C++, shares detailed code examples that you can then plug into your own code, and reveals the significant changes to C++ that accompany the latest release. You'll discover how to design and build applications that solve real-world problems and then implement the solution using the full capabilities of the language.
Keywords: C++ (Computer program language),C++ (Ngôn ngữ lập trình máy tính)